(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this work, we deal with two-point boundary problem for a finite nabla fractional difference equation. First, we establish an associated Green's function and state some of its properties. Under suitable conditions, we deduce the existence and non-existence of positive solutions to the considered problem. Finally, we construct a few examples to illustrate the established results.